Effect of Hemicellulase Enzyme in Flotation Deinking of Laser-printed Paper - Chandranupap, Pravitra; Chandranupap, Panitnad (Applied Science and Engineering Progress, 2021)
Deinking is one of the most important steps in paper recycling process. Novel deinking method such as emzymatic deinking has grown more and more important in environmentally friendly paper recycling. The aim of this work was to investigate the effect of hemicellulase enzyme on the efficiency of ink removal from laser-printed paper in flotation deinking process. The influence on pulp and mechanical properties of deinked paper such as freeness, tensile index and tear index are also studied. The experiments performed at the dosages of hemicellulase enzyme from 0 to 0.15% with the concentration of nonionic surfactant (Tween-80) of 1.75% (Base on oven-dried weight of paper). The results obtained in this work revealed the enhancement of ink removal efficiency (11.3–95.3%), as indicated by the decreasing of the effective residual ink concentration (ERIC) as compared to non-deinked paper. Moreover, the results showed the improvement in freeness (3.7–13.2%), tensile index (5.2–18.1%), and tear index (19–25.6%) with respect to the control condition obtained with the absence of enzyme. These improvements were achieved considerably after flotation process but tended to drop down when the dosage of enzyme was too much. The maximum deinking efficiency (about 95%) was found at 0.1% hemicellulase enzyme (based on oven-dried weight of paper) which the mechanical properties after flotation deinking process increased about 25% and 18% in tear index and tensile index, respectively, as compared to control.